Cochrane Database of Systematic Reviews 2003
DOI: 10.1002/14651858.cd003412
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for basal cell carcinoma of the skin

Abstract: Interventions for basal cell carcinoma of the skin (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
89
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(96 citation statements)
references
References 38 publications
0
89
0
Order By: Relevance
“…In addition, PDT, imiquimod, and 5-FU have the benefit of a better cosmetic outcome compared with surgical excision. 4 However, recurrence rates of noninvasive treatments are higher compared with surgery and range from 13% to 27% at 1-year posttreatment. 5,6 Little is known about histologic characteristics of sBCC that may influence treatment response of noninvasive therapies.…”
mentioning
confidence: 99%
“…In addition, PDT, imiquimod, and 5-FU have the benefit of a better cosmetic outcome compared with surgical excision. 4 However, recurrence rates of noninvasive treatments are higher compared with surgery and range from 13% to 27% at 1-year posttreatment. 5,6 Little is known about histologic characteristics of sBCC that may influence treatment response of noninvasive therapies.…”
mentioning
confidence: 99%
“…A recent Cochrane review concluded that excision is superior to the other treatment modalities [9]. To date there is just one randomised controlled trial (RCT) comparing MMS to standard surgical excision and this showed that MMS is better for treating recurrent BCCs but only trended toward superiority for primary BCCs [10].…”
Section: Discussionmentioning
confidence: 99%
“…The Cochrane reviews [9,12] acknowledge that there is a paucity of RCT evidence; however, there have been several sizeable prospective case series and much literature published in Australia where BCC is a major public health concern [13,14,15]. Large non-randomised and retrospective studies suggest that standard excision has recurrence rates of 3-10 % for primary tumours and [17 % for recurrent tumours, [8,16,17] whereas, MMS yields recurrence rates of 1 % for primary tumours [18] and 5-7 % for recurrent tumours [19,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is generally regarded as the best option following surgery [5]. The superiority of RT over some other treatment modalities has been illustrated in data such as a randomized controlled trial comparing RT with cryotherapy.…”
Section: Radiotherapy Treatment Of Bccmentioning
confidence: 99%